Paternal monoallelic expression of the paired immunoglobulin-like receptors PIR-A and PIR-B - Chen, Ching-Cheng (The National Academy of Sciences, 1999)
A diverse pattern of polymorphism is defined for the paired Ig-like receptors (PIRs) that serve as activating (PIR-A) and inhibitory (PIR-B) receptors on B lymphocytes, dendritic cells, and myeloid-lineage cells in mice. The monoclonal anti-PIR antibody 10.4 is shown to recognize an allelic PIR-A/PIR-B determinant on cells from BALB/c but not C57BL/6 mice. Other strains of inbred mice also can be typed on the basis of their expression of this PIR allelic determinant. Analysis of (BALB/c × C57BL/6) F(1) hybrid offspring indicates that PIR molecules bearing the paternal PIR allotype are expressed whereas PIR-A and PIR-B molecules bearing the maternal allotype are not. The monoallelic expression of the polymorphic PIR-A and PIR-B molecules, and possibly of their human Ig-like transcript/leukocyte Ig-like receptor/monocyte/macrophage Ig-like receptor and killer cell inhibitory receptor relatives, may influence innate and specific immune responses in outbred populations.